2016
DOI: 10.1128/jvi.01028-16
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated Virus Vectors Efficiently Transduce Mouse and Rabbit Sensory Neurons Coinfected with Herpes Simplex Virus 1 following Peripheral Inoculation

Abstract: Following infection of epithelial tissues, herpes simplex virus 1 (HSV-1) virions travel via axonal transport to sensory ganglia and establish a lifelong latent infection within neurons. Recent studies have revealed that, following intraganglionic or intrathecal injection, recombinant adeno-associated virus (rAAV) vectors can also infect sensory neurons and are capable of stable, longterm transgene expression. We sought to determine if application of rAAV to peripheral nerve termini at the epithelial surface w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…(AAV-LATRz-235). We have previously demonstrated that AAV applied to the rabbit eye is efficiently transported to the TG and can efficiently transduce Ͼ70% of the total neurons (22). Seventeen days after treatment with AAV, the rabbit eyes were iontophoresed with epinephrine and swabbed daily for 12 days to collect tears.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(AAV-LATRz-235). We have previously demonstrated that AAV applied to the rabbit eye is efficiently transported to the TG and can efficiently transduce Ͼ70% of the total neurons (22). Seventeen days after treatment with AAV, the rabbit eyes were iontophoresed with epinephrine and swabbed daily for 12 days to collect tears.…”
Section: Resultsmentioning
confidence: 99%
“…Adeno-associated virus (AAV) vectors were used to deliver a ribozyme to target the HSV-1 LAT being expressed in latently infected sensory neurons. This approach exploits the ability of some serotypes of AAV to be inoculated on the skin or in the cornea, subsequently taken up by nerve termini, and ultimately transported by axonal transport to the neuronal cell bodies, where the HSV-1 latent infection resides (22). We have previously used this approach to deliver small interfering RNAs (siRNAs) to latently infected neurons in the rabbit trigeminal ganglia (TG) to knockdown the cellular insulator protein CTCF (23).…”
mentioning
confidence: 99%
“…Several viral and nonviral systems have been employed for CRIPR Cas9 delivery. Viral vectors such as lentiviral, adenoviral, and adeno associated virus (AAV) are being widely used as delivery systems with promising results . However, the application of lenti and adeno viral vectors is limited due to low viral titers, risk of internal mutation, long duration of CRISPR/Cas9 activity, and stimulation of the immune system, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…Viral vectors such as lentiviral, adenoviral, and adeno associated virus (AAV) are being widely used as delivery systems with promising results. [138][139][140][141] However, the application of lenti and adeno viral vectors is limited due to low viral titers, risk of internal mutation, long duration of CRISPR/Cas9 activity, and stimulation of the immune system, respectively. 138,[142][143][144] Given the promising characteristics of AAV such as versatility, less toxicity, minimal immunogenicity and high tropism for neurons, hepatocytes, and epithelial cells, it can be regarded as an attractive delivery system for introduction of anti-HSV, anti-HBV, and anti-HPV to the infected cells.…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%
“…As many of these are neurotropic (Salganik et al, ), they are ideal candidates to infect latent HSV and VZV‐infected neurons. Indeed, several studies show efficient delivery of AAV to both the trigeminal and dorsal ganglia by locally infecting the cornea or the footpad of mice, rats, and rabbits (Mason et al, ; Watson et al, ), suggesting that safe and efficient delivery of AAV vectors carrying anti‐herpesviral CRISPR/Cas9 may be possible to cripple or even clear neurotropic alphaherpesviruses from cells. Several AAV serotypes can also infect immune cell types, albeit to low efficiency (Pandya, Ortiz, Ling, Rivers, & Aslanidi, ; Veldwijk et al, ), opening up a way for targeting of latent HCMV‐infected or EBV‐infected cells.…”
Section: Application Of Crispr/cas9 As Anti‐herpesvirus Therapy: Limimentioning
confidence: 99%